Multi-objective Optimization of Combined Gray-green Infrastructure Rainwater System for Yuhuazhai Depot of Xi’an Metro - LYU Jiajie (Chengshi guidao jiaotong yanjiu)
［Objective］ Acceleration of the urbanization process and frequent occurrence of urban flood disasters impose higher requirements on the rainwater system of urban rail transit depots. It is necessary to conduct a detailed study on the schemes of the depot rainwater system. ［Method］ Based on the rainwater management concept by combining gray infrastructure and green infrastructure, the hydrological simulation software SWMM (storm water management model) is used to simulate the hydrological processes under various combination schemes for Yuhuazhai Depot of Xi’an Metro Line 3. A multi-objective optimization method is designed through the response surface method. Combined with the particle swarm optimization algorithm, the Matlab software is used to optimize the configuration of the green infrastructure within the depot in order to achieve effective control over the total runoff volume, peak flood, TSS (total suspended solids) and costs. ［Result & Conclusion］ Through multi-objective optimization and comparison, the optimal gray-green combination rainwater system scheme for Yuhuazhai Depot of Xi’an Metro is determined. In particular, the combined layout of permeable pavements and retention ponds should be given priority within the depot. This scheme not only meets the requirements of GB 51345—2018 Assessment Standard for Sponge City Construction Effect, but also maximizes the economic benefits.